Spermatogenesis in the marine snail Adelomelon ancilla (Volutidae) from Patagonia - Zabala, Maria Soledad (2011)
This study describes euspermatogenesis and paraspermatogenesis in Adelomelon ancilla (Volutidae) and compares them with the same processes in other caenogastropods. Spermatogenesis in A. ancilla followed the general developmental pattern of caenogastropods. The pattern of nuclear condensation involves granular, fibrillar, lamellar and homogenous electron-dense phases. Acrosome development begins with the posteriorly located proacrosomal vesicle arising from the Golgi complex in euspermatids. The proacrosomal vesicle develops into a preattachment acrosome which, together with the Golgi body, later moves towards the apex of the nucleus. In the early stage of paraspermatogenesis, the pattern of chromatin distribution in dense patches, together with the cytoplasmatic characteristics of paraspermatogonia, allows the recognition of the apyrene line from the euspermatogonia. Later features, including the peripheral condensation of nuclear chromatin followed by nuclear invagination, the posterior breakdown into nuclear vesicles (‘caryomerites’), centriole multiplication and the synthesis of secretory products, are the most conspicuous changes in the process of paraspermatogenesis.